2020
DOI: 10.2196/17593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Brief Electronic Mindfulness-Based Intervention on Relieving Prenatal Depression and Anxiety in Hospitalized High-Risk Pregnant Women: Exploratory Pilot Study

Abstract: Background Peripartum depression and anxiety disorders are highly prevalent and are correlated with adverse maternal and neonatal outcomes. Antenatal care in Germany does not yet include structured screening and effective low-threshold treatment options for women facing peripartum depression and anxiety disorders. Mindfulness-based interventions (MBIs) are increasingly becoming a focus of interest for the management of such patients. Studies have shown a decrease in pregnancy-related stress and anx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Zhang et al, 2019), while Beattie et al (2017) did not show a positive effect of mindfulness-based interventions on perceived stress and Duncan et al (2017) did not show a positive result on pain catastrophizing. This result does not seem to be affected by the weak ratings of the studies from Goetz et al (2020), Sobhani et al (2019 and Warriner et al (2018).…”
Section: Online Vs Offlinementioning
confidence: 71%
See 4 more Smart Citations
“…Zhang et al, 2019), while Beattie et al (2017) did not show a positive effect of mindfulness-based interventions on perceived stress and Duncan et al (2017) did not show a positive result on pain catastrophizing. This result does not seem to be affected by the weak ratings of the studies from Goetz et al (2020), Sobhani et al (2019 and Warriner et al (2018).…”
Section: Online Vs Offlinementioning
confidence: 71%
“…The included studies show mixed results regarding mindfulness-based interventions and their positive effect on anxiety/fear and stress. While several authors found positive influences (Goetz et al, 2020;Krusche et al, 2018;Price et al, 2019;Sobhani et al, 2019;Warriner et al, 2018;Yang et al, 2019;Zarenejad et al, 2020;Zemestani, 2019;J.-Y. Zhang et al, 2019), two studies did not show positive effects of mindfulness-based interventions on perceived stress (Beattie et al, 2017) or on pain catastrophizing (Duncan et al, 2017).…”
Section: Categories Of Interventionsmentioning
confidence: 96%
See 3 more Smart Citations